Program Kartu Keluarga Sejahtera: Efektifkah? (Bukti Empiris di Kampung Mulia Kencana Kabupaten Mimika) - Pabendon, Tharsisius; Allopaa, Restu Tivani (STIE Jambatan Bulan, 2022)
This study aims to analyze the effectiveness of the Family Welfare Card Program (KKS) specific to the Family Hope Program (PKH) by beneficiaries in Kampung Mulia Kencana. The research method used in this research is the descriptive research method. Data collection techniques using documentation, interviews, and questionnaires. The analytical instrument uses the effectiveness formula. The results of this study found that the socialization of PKH was at 61%, 96% of KPM used aid fundsbyh PKH's objectives, the rate of recipients of assistance was 85% on target, and the level of program monitoring was at 55%. Meanwhile, if calculated as a whole, the effectiveness of the Family Hope Program in Kampung Mulia Kencana is 79%, which based on the ratio of the effectiveness levels means that the implementation of the Family Hope Program in Kampung Mulia Kencana is less effective.